Trade in Services-Economic Growth Nexus: An Analysis of the Growth Impact of Trade in Services in SADC Countries - Maune, Alexander (Journal of Economics and Behavioral Studies, 2019)
The article analysed the trade in services led growth in ten selected countries in the Southern African Development Community region using econometric regression models. Panel data obtained from the World Bank and United Nations Conference on Trade and Development databases for the period 1992 to 2015 was analysed. Five variables were used in the econometric analysis. The marginal effects of service and goods exports were positive while those of goods and service imports were negative and highly significant as was expected from literature. Service exports registered an impact that was almost threefold that of service imports and greater than goods exports. Policy-makers are encouraged to, clearly define their trade in service strategy and reduce or remove trade restrictions. The study is of importance to researchers, the private sector and government policymakers.